Matrices Long Questions (Question 1 – 4)


Question 1:
It is given that matrix A = ( 3 1 5 2 )
(a) Find the inverse matrix of A.
(b) Write the following simultaneous linear equations as matrix equation:
3uv = 9
5u – 2v = 13
Hence, using matrix method, calculate the value of u and v.

Solution
:

(a)
A 1 = 1 3 ( 2 ) ( 5 ) ( 1 ) ( 2 1 5 3 ) = 1 ( 2 1 5 3 ) = ( 2 1 5 3 )

(b)

( 3 1 5 2 ) ( u v ) = ( 9 13 ) ( u v ) = 1 ( 2 1 5 3 ) ( 9 13 ) ( u v ) = 1 ( ( 2 ) ( 9 ) + ( 1 ) ( 13 ) ( 5 ) ( 9 ) + ( 3 ) ( 13 ) ) ( u v ) = 1 ( 5 6 ) ( u v ) = ( 5 6 ) u = 5 , v = 6


Question 2:
It is given that matrix A = ( 2 5 1 3 ) and matrix B = m ( 3 k 1 2 ) such that AB = ( 1 0 0 1 )
(a) Find the value of m and of k.
(b) Write the following simultaneous linear equations as matrix equation:
2u – 5v = –15
u + 3v = –2
Hence, using matrix method, calculate the value of u and v.

Solution:

(a) Since AB = ( 1 0 0 1 ) , B is the inverse of A.

m = 1 ( 2 ) ( 3 ) ( 5 ) ( 1 ) = 1 11
k = 5

(b)
( 2 5 1 3 ) ( u v ) = ( 15 2 ) ( u v ) = 1 11 ( 3 5 1 2 ) ( 15 2 ) ( u v ) = 1 11 ( ( 3 ) ( 15 ) + ( 5 ) ( 2 ) ( 1 ) ( 15 ) + ( 2 ) ( 2 ) ) ( u v ) = 1 11 ( 55 11 ) ( u v ) = ( 5 1 ) u = 5 , v = 1


Question 3:
It is given that Q  ( 3 2 6 5 ) = ( 1 0 0 1 ) , where Q is a 2 x 2 matrix.
(a) Find Q.
(b) Write the following simultaneous linear equations as matrix equation:
3u + 2v = 5
6u + 5v = 2
Hence, using matrix method, calculate the value of u and v.

Solution
:

(a) 
Q = ( 3 2 6 5 ) 1 Q = 1 3 ( 5 ) 2 ( 6 ) ( 5 2 6 3 ) Q = 1 3 ( 5 2 6 3 ) Q = ( 5 3 2 3 2 1 )

(b)

( 3 2 6 5 ) ( u v ) = ( 5 2 ) ( u v ) = 1 3 ( 5 2 6 3 ) ( 5 2 ) ( u v ) = 1 3 ( ( 5 ) ( 5 ) + ( 2 ) ( 2 ) ( 6 ) ( 5 ) + ( 3 ) ( 2 ) ) ( u v ) = 1 3 ( 21 24 ) ( u v ) = ( 7 8 ) u = 7 , v = 8


Question 4:
It is given that Q ( 3 2 5 4 ) = ( 1 0 0 1 )  , where Q is a 2 × 2 matrix.
(a) Find the matrix Q.
(b) Write the following simultaneous linear equations as matrix equation:
3x – 2y = 7
5x – 4y = 9
Hence, using matrix method, calculate the value of x and y.

Solution:

(a)
Q = 1 3 ( 4 ) ( 5 ) ( 2 ) ( 4 2 5 3 ) = 1 2 ( 4 2 5 3 ) = ( 2 1 5 2 3 2 )

(b)

( 3 2 5 4 ) ( x y ) = ( 7 9 ) ( x y ) = 1 2 ( 4 2 5 3 ) ( 7 9 ) ( x y ) = 1 2 ( ( 4 ) ( 7 ) + ( 2 ) ( 9 ) ( 5 ) ( 7 ) + ( 3 ) ( 9 ) ) ( x y ) = 1 2 ( 10 8 ) ( x y ) = ( 5 4 ) x = 5 , y = 4

Leave a Reply

Your email address will not be published. Required fields are marked *